Determinant variables in the responsible consumption of artificial intelligence (AI) from the perspective of non-specialized users in Colombia - Guzmán Rincón, Alfredo; Amado Mateus, Marelby; Martín-Caro Álamo, Ester (Emerald Publishing Limited, 2025)
This study analyses the determinant variables influencing responsible AI consumption from the perspective of non-specialised users in Colombia. Using a quantitative cross-sectional design and a structured questionnaire applied to 485 participants, the research evaluates sustainable, ethical and rational dimensions of AI consumption. A multiple linear regression model identifies rational consumption as the most influential predictor, followed by ethical and sustainable dimensions. The findings highlight the need for digital literacy initiatives and regulatory measures to promote responsible AI use in emerging economies.
Keywords: Responsible consumption; Rational consumption; Sustainable consumption; Ethical consumption; Artificial intelligence; https://purl.org/pe-repo/ocde/ford#5.02.04